Fungsionalisme Sigmund Freud Tentang Agama Dalam Buku Nine Theories Of Religion Karya Daniel L. Pals - Najihah, Bannan Naelin; Truna, Dody S; Rosyad, Rifki (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research reveals Sigmund Freud's theories and views on religion in Daniel L.Pals‘ Nine Theories of Religion and analyses them using Emil Durkheim and William James’ functionalism theories. The type of method used in this research is descriptive qualitative research with content analysis techniques and library research. The results of this study show that Freud identified an internal conflict between the id, ego, and superego similar to Durkheim's concept of social institutions that balance individual needs with social norms, seeing religion as a mechanism to strengthen social cohesion. James emphasised adaptation and individual psychological functioning, helping to understand Freud's analysis of personality conflict and the Oedipus complex as an attempt at individual adaptation to the social environment. Although Freud saw religion as a collective neurosis and illusion, from Durkheim's perspective, religion plays an important role in strengthening social solidarity, and from James' perspective, religion provides significant meaning and moral strength for individuals, helping them to face life's challenges and adapt to their social environment. Thus, religion serves as a mechanism for maintaining psychological and social stability, providing meaning and structure for individuals in a complex society.